Fabrication of Au-decorated SnO2 nanoparticles with enhanced n-buthanol gas sensing properties. (October 2019) - Lian, Xiaoxue; Li, Yan; Zhu, Junwu; Zou, Yunling; An, Dongmin; Wang, Qiong
Abstract: Stannic oxide nanoparticles with the different Au decorating contents are prepared by a simple hydrothermal method in this paper. The products are characterized by X-ray diffraction (XRD), energy dispersive spectrum (EDS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The XRD patterns reveal that all the products are tetragonal phase of rutile SnO2 crystal structure. The gas-sensing performance of the Au-decorated SnO2 nanoparticles for volatile organic compounds (VOCs) are studied. At its optimal operation temperature of 240 o C, the sensing properties of the Au-decorated SnO2 nanoparticles to n-buthanol gas show a good gas sensing performances as low detection limit (1ppm), good selectivity and good repeatability. The highest sensing response of 6.0 at. % Au-decorated SnO2 nanoparticles (251.23 for 200 ppm to n-buthanol) is over 21 times higher than that of pure SnO2 (11.5). All results prove the potential of using Au-decorated SnO2 for n-buthanol gas detection.